Blood Donations and Incentives: Evidence from a Field Experiment - Lorenz Goette; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2008)
There is a longstanding concern that material incentives might undermine prosocial motivation, leading to a decrease in blood donations rather than an increase. This paper provides an empirical test of how material incentives affect blood donations in a large-scale eld experiment spanning three months and involving more than 10,000 previous donors. We examine two types of incentive: a lottery ticket and a free cholesterol test. Lottery tickets signi cantly increase donations, in particular among less motivated donors. The cholesterol test leads to no discernable impact on usable blood donations. If anything, it creates a small negative selection effect in terms of donations that must be discarded.
Keywords: C93; D64; H41; I18; 330; prosocial behavior; blood donations; material incentives; eld experiment; Blutspendedienst; Soziales Verhalten; Anreiz; Test